2023
DOI: 10.1177/07334648221148163
|View full text |Cite
|
Sign up to set email alerts
|

Working Conditions Affecting Home Care Workers’ Stress and Turnover Intention

Abstract: This study explored how working conditions influence the psychological outcomes of paid family and non-family home care workers, focusing on the interaction between institutional and recipient effects. Using data from the 2019 Korean Long-Term Care Survey (N = 998), we performed regression analyses on home care workers’ stress and turnover intention. For both types of home care-workers, inadequate working conditions and high occupational hazards influenced stress, while good working conditions and low occupati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Foa found that positive relationships with colleagues and training favor job satisfaction, while workload, lack of training, and reduction of rest time create dissatisfaction and even increase burnout [ 21 ]. Lee et al reported that several work conditional factors like wage, working hours, and working intensity influence the turnover intention of home care workers [ 22 ]. Additionally, intrapersonal factors, including ageism, burnout, and mood, have been associated with job satisfaction and intention to leave directly or indirectly.…”
Section: Introductionmentioning
confidence: 99%
“…Foa found that positive relationships with colleagues and training favor job satisfaction, while workload, lack of training, and reduction of rest time create dissatisfaction and even increase burnout [ 21 ]. Lee et al reported that several work conditional factors like wage, working hours, and working intensity influence the turnover intention of home care workers [ 22 ]. Additionally, intrapersonal factors, including ageism, burnout, and mood, have been associated with job satisfaction and intention to leave directly or indirectly.…”
Section: Introductionmentioning
confidence: 99%